Reflection on the Financial Issues in the Enlarging European Union - András Inotai (Romanian Journal of European Affairs)
Although access to EU financial resources is by far not the only objective of the new member countries, it is considered to be an important instrument to accelerate growth and economic modernization and support the catching up process to current EU levels. The article deals with the current structure, constraints and contradictions of the EU budget from 2000 to 2006, both from the background of global developments, intra-EU interests and the requirements of successful accession. Special attention is paid to the preparation of the new member countries to efficiently and quickly absorb available EU resources (both in agriculture and in the framework of structural and cohesion funds). It is pointed out that, although net resource flow will substantially fall short of that to the more developed but still net beneficiary present member countries, it could generate budgetary constraints in the new member countries, particularly in the first and decisive years of membership. The last chapter addresses some key issues, concerns and uncertainties of the volume and structure of the budget for the next period covering the years from 2007 to 2013. In addition, it outlines a proposal for creating a new objective within the coming budget to co-finance the cross-country and harmonized development of infrastructure of the new and still candidate member countries. In case of a high level of regional cooperation between East, Central and Southeastern European countries, this seems to be the most powerful argument to fundamentally change the pattern of distribution of the EU budget in favour of the less developed but rapidly developing new member countries.